Effects of Perceived Self-Efficacy in Weight Controlling Promoting Program on Consumption Behaviors, Waist Circumfernce, and Body Mass Index among Obese Elderly - Sukkum, Worarat; Kespichayawattana, Jiraporn (Journal of Health Science of Thailand, 2018)
The purpose of this experimental research using two group pretest-posttest design were to compare the consumption behaviors, waist circumference, and body mass index among obese elderly between those who received the perceived self-efficacy in weight controlling promoting program and those who received routine service care. Self - Efficacy Theory of Bandura (1997) were utilized to develop the intervention. Duration of this study was from 6 June to 18 July 2008. Subjects consisted of 42 obese elderly which were randomly assigned to control and experimental groups, 21 for each group. Participants were matched by sex, age, body mass index, and education. The experimental group received the perceived self-efficacy in weight controlling promoting program which was developed by the researcher. An instruments of this study was comprised of 2 parts. The intervention included lesson plans, flip charts, model of food, model of person and handbook, and the data collecting instruments was Consumption Behaviors Measurement (CBI) which was tested for content validity and reliability. Cronbach’s alpha coefficients of the CBI were 0.78. Data were analyzed using mean, standard deviation and t-test. It was found that the mean score of consumption behaviors of obese elderly after receiving the perceived self-efficacy in weight controlling promoting program was significantly higher than that before receiving the program and that of the control group (p < 0.05) and The means of waist circumference and body mass index of obese elderly after receiving the perceived self-efficacy in weight controlling promoting program were significantly lower than those before receiving the program and those of the control group (p < 0.05)